THE PROPERTIES OF CHARCOAL FROM THE BLACK LIQUOR OF THE SODA PULPING OF RICE STRAW - Nyoman Jaya Wistara; Gokma Silaban; Gustan Pari (Reaktor, 2013)
The main goal of the present works was to determine chemical changes, thermal decomposition, and the content of moisture, ash, volatile, fixed carbon and calorific value of soda pulping black liquor of the rice straw. Neutralized black liquor was dried to a moisture content of 10% and then pyrolized at 106oC-750oC. It was found that calorific value, fixed carbon, volatile mater, and moisture content were in the range of 2782-4716 cal/g, 49.2-81.6%, 15.5-47.5%, and 0.2-3.5%, respectively. Ash content was not influenced by the temperature of pyrolysis and was thought to depend on its initial silicate content. The weight loss of pulp was higher than that of black liquor. Extreme weight loss has been found in the temperature of 200-400oC. Noticeable functional groups changes were found with the increasing temperature of pyrolysis. Hydroxyl group completely disappeared at 300oC and above. Carbonyl related groups were also disappeared at 300-500oC, but it was reformed at 650 and 750oC. It might be brought about by the deformation of chemical bonding of oxygen ring in lignin structures. SIFAT-SIFAT ARANG LINDI HITAM DARI PEMASAKAN JERAMI DENGAN LARUTAN SODA API. Penelitian ini bertujuan untuk menentukan perubahan sifat kimia, dekomposisi termal dan kadar air, abu, zat terbang, karbon terikat serta nilai kalor arang lindi hitam pemasakan soda jerami padi. Dalam penelitian ini, lindi hitam netral dikeringkan (kadar air 10%), kemudian dipirolisis pada selang suhu 100-750oC di dalam reaktor berpengatur suhu. Hasil penelitian menunjukkan bahwa nilai kalor, karbon terikat, zat terbang dan kadar air masing-masing berselangdari 2782-4716 cal/g, 49,2-81,6%, 15,5-47,5%, dan 0,2-3,5%. Kadar abu tidak dipengaruhi oleh suhu pirolisis dan diduga bergantung pada kadar silika bahan bakunya. Nilai kalor meningkat dengan meningkatnya kadar karbon terikat. Perilaku kehilangan berat arang dari lindi hitam berbeda dengan perilaku kehilangan berat pulp jerami. Kehilangan berat pulp lebih tinggi dari kehilangan berat arang lindi hitam. Kehilangan berat yang tajam terjadi pada selang suhu 200-400oC. Perubahan gugus fungsi yang nyata terjadi dengan meningkatnya suhu pirolisis. Gugus hidroksil menghilang pada suhu 300oC atau lebih. Gugus terkarbonilasi menghilang pada suhu 300-500oC, tetapi terbentuk kembali pada suhu 650oC dan 750oC. Hal ini kemungkinan disebabkan oleh deformasi ikatan kimia oksigen di dalam cincin dari struktur lignin.